A study on incorporating ICT in teaching methodologies at universities of Quetta - Saeed, Nausheen; Nasim, Farrukh; Hussain, Walayat; Azeem, Samina (Journal of Advanced Computer Science & Technology, 2015)
This paper presents a study on the use of ICT in teaching methodology by the faculty of universities in Quetta, Pakistan. A Survey about the impact of ICT usage was conducted in three major public universities of Quetta - University Of Balochistan, Sardar Bahadur Khan Women University, and Balochistan University of Information Technology, Engineering and Management Sciences, focusing the faculty and the students. The study shows that ample ICT facilities are available to the faculties in these universities and the teachers incorporate different ICT tools in their teaching methodologies. Teachers and students believe that ICT has played a vital role in improving the quality of education while there remain some areas of improvement like University web portals, access to digital libraries for the students and online student management systems.